Home » Past Questions » Mathematics » Simplify 7\(\frac{1}{12}\) - 4\(\frac{3}{2}\) + 2\(\frac{1}{2}\)

Simplify 7\(\frac{1}{12}\) - 4\(\frac{3}{2}\) + 2\(\frac{1}{2}\)


Question

Simplify 7\(\frac{1}{12}\) - 4\(\frac{3}{2}\) + 2\(\frac{1}{2}\)

Options

A) 4

B) 4\(\frac{1}{6}\)

C) 4\(\frac{5}{6}\)

D) 5\(\frac{1}{6}\)

The correct answer is C.

Explanation:

7\(\frac{1}{12}\) - 4\(\frac{3}{2}\) + 2\(\frac{1}{2}\)
Take care of the whole numbers
7 - 4 + 2 = 5
therefore, 5\(\frac{1}{12}\) - \(\frac{3}{4}\) + \(\frac{1}{2}\)
LCM = 12
5\(\frac{1 - 9 + 6}{12}\)
4\(\frac{13 - 9 + 6}{12}\)
= 4\(\frac{10}{12}\)
or = 4\(\frac{5}{6}\)

More Past Questions:


Discussion (2)

  • why don't we convert the mixed fraction into an improper fraction before using BODMAS

    Reply
    Like
  • 7\(\frac{1}{12}\) - 4\(\frac{3}{2}\) + 2\(\frac{1}{2}\)
    Take care of the whole numbers
    7 - 4 + 2 = 5
    therefore, 5\(\frac{1}{12}\) - \(\frac{3}{4}\) + \(\frac{1}{2}\)
    LCM = 12
    5\(\frac{1 - 9 + 6}{12}\)
    4\(\frac{13 - 9 + 6}{12}\)
    = 4\(\frac{10}{12}\)
    or = 4\(\frac{5}{6}\)

    Reply
    Like